2022
DOI: 10.1099/jmm.0.001513
|View full text |Cite
|
Sign up to set email alerts
|

First identification of bla NDM-5 producing Escherichia coli from neonates and a HIV infected adult in Tanzania

Abstract: Introduction. Carbapenem-resistant members of the family Enterobacteriaceae are emerging as a global public-health threat and cause substantial challenges in clinical practice. Gap Statement. There is a need for increased and continued genomic surveillance of antimicrobial resistance genes globally in order to detect outbreaks and dissemination of clinically important resistance genes and their associated mobile genetic elements in human pathogens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Four isolates showed co-existence with blaNDM-1 and blaOXA-1 producing E. coli in the molecular characterization; two isolates were associated with blaNDM-1 and blaOXA-1, and one was blaNDM-4 co-existing with blaOXA-1 among K. pneumonia; one isolate was associated with blaNDM-5 and blaOXA-1, and one was blaNDM-1 co-existing with blaOXA-1. The previously discovered blaNDM and blaOXA-1.15NDM-5, which were first discovered in E. coli, are also found in Bangladesh (Manyahi et al 2022). These alterations were responsible for the high resistance of NDM-5 bacteria compared to NDM-1 bacteria (Hornsey, Phee, & Wareham 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Four isolates showed co-existence with blaNDM-1 and blaOXA-1 producing E. coli in the molecular characterization; two isolates were associated with blaNDM-1 and blaOXA-1, and one was blaNDM-4 co-existing with blaOXA-1 among K. pneumonia; one isolate was associated with blaNDM-5 and blaOXA-1, and one was blaNDM-1 co-existing with blaOXA-1. The previously discovered blaNDM and blaOXA-1.15NDM-5, which were first discovered in E. coli, are also found in Bangladesh (Manyahi et al 2022). These alterations were responsible for the high resistance of NDM-5 bacteria compared to NDM-1 bacteria (Hornsey, Phee, & Wareham 2011).…”
Section: Discussionmentioning
confidence: 95%
“…ESBL-producing Gram-negative infections are an increasing clinical problem in Malawi, and there is a significant unmet need for access to carbapenem antimicrobials to treat them. Carbapenemase producing Enterobacterales including E. coli (bla NDM-5 in E. coli ST636) have recently been described in other regions of Malawi [52], and bla NDM-5 is increasingly being identified across sSA [53]. The presence of carbapenemases in this collection despite minimal local carbapenem use highlights the need for ongoing surveillance as these last-line antimicrobials are introduced.…”
Section: Discussionmentioning
confidence: 97%
“…coli ( bla NDM-5 in E. coli ST636) have recently been described in other regions of Malawi [52], and bla NDM-5 is increasingly being identified across sSA [53]. The presence of carbapenemases in this collection despite minimal local carbapenem use highlights the need for ongoing surveillance as these last-line antimicrobials are introduced.…”
Section: Discussionmentioning
confidence: 99%
“…MLST showed that the two CREC isolates (CREC-18 and 19) belonged to ST167, and the remaining 2 isolates were characterized with ST361 (CREC-20) and ST648 (CREC-17). The E. coli ST167 clone is emerging throughout the world, being frequently recognized for having a link with carbapenem resistance [ 15 , 16 ] and for being involved in the transmission of the bla NDM-1 and bla NDM-5 genes in hospitals [ 17 ]. It has been demonstrated that the ST167 has peculiar virulence characteristics which facilitate its evolution to a high-risk clone with widespread colonization and infection capabilities [ 18 ].…”
Section: Discussionmentioning
confidence: 99%